STOCHASTIC SIMULATION MODELING OF CELL TELOMERE SHORTENING MECHANISMS IN AGEING AND DISTURBANCE DEVELOPMENT PROCESSES - Alexander Alexandrovich Butov; Mikhail Andreyevich Karev; Sergey Alexandrovich Khrustalev (Advanced Engineering Research, 2014)
Some issues of applying the stochastic simulation modeling to the description and stud ying of DNA’s end structures (telomeres) shortening mechanisms are considered. The aim of this research is to study — on the base of the st ochastic and simulation modeling — processes in the cells leading to the telomeres’ length shortening, and as a co nse quence, to decreasing the proliferative capacity, and developing pathologies including oncologic one s. The mat hematical model is described in the semimartingale terms. The analysis of the modeling results is bas ed on their comparison to the biological expe riments data. The formed cell distribution in accordance to their telomeres’ length is compared with the e x perimental data obtained through the tests performed with human fibroblast - culture using Levy — Prokhorov metric. The study results can be used in bi omedical research on ageing, and on developing var ious pathologies, as well as in solving a number of problems in the field of gero n tology.